C4b-binding protein inhibits particulate- and crystalline-induced NLRP3 inflammasome activation - Bierschenk, Damien; Papac-Milicevic, Nikolina; Bresch, Ian P.; Kovacic, Valentina; Bettoni, Serena; Dziedzic, Mateusz; Wetsel, Rick A.; Eschenburg, Susanne; Binder, Christoph J.; Blom, Anna M.; King, Ben C. (Frontiers in Immunology, 2023)
Dysregulated NLRP3 inflammasome activation drives a wide variety of diseases, while endogenous inhibition of this pathway is poorly characterised. The serum protein C4b-binding protein (C4BP) is a well-established inhibitor of complement with emerging functions as an endogenously expressed inhibitor of the NLRP3 inflammasome signalling pathway. Here, we identified that C4BP purified from human plasma is an inhibitor of crystalline- (monosodium urate, MSU) and particulate-induced (silica) NLRP3 inflammasome activation. Using a C4BP mutant panel, we identified that C4BP bound these particles via specific protein domains located on the C4BP α-chain. Plasma-purified C4BP was internalized into MSU- or silica-stimulated human primary macrophages, and inhibited MSU- or silica-induced inflammasome complex assembly and IL-1β cytokine secretion. While internalized C4BP in MSU or silica-stimulated human macrophages was in close proximity to the inflammasome adaptor protein ASC, C4BP had no direct effect on ASC polymerization in in vitro assays. C4BP was also protective against MSU- and silica-induced lysosomal membrane damage. We further provide evidence for an anti-inflammatory function for C4BP in vivo, as C4bp-/- mice showed an elevated pro-inflammatory state following intraperitoneal delivery of MSU. Therefore, internalized C4BP is an inhibitor of crystal- or particle-induced inflammasome responses in human primary macrophages, while murine C4BP protects against an enhanced inflammatory state in vivo. Our data suggests C4BP has important functions in retaining tissue homeostasis in both man and mice as an endogenous serum inhibitor of particulate-stimulated inflammasome activation.